Burnout, work engagement and life satisfaction among Spanish teachers: The unique contribution of core self-evaluations. - Peláez-Fernández, María Ángeles; Mérida-López, Sergio; Rey-Peña, Lourdes; Extremera-Pacheco, Natalio (Elsevier, 2022)
The aim of this study was to examine burnout and engagement dimensions as predictors of life satisfaction in a sample of 531 Spanish teachers. We also aimed to examine the additional contribution of core self-evaluations on life satisfaction, above and beyond socio-demographic variables and burnout and engagement dimensions. Results of hierarchical regression analyses indicated that core self-evaluations explained a substantial and unique amount of variance in life satisfaction beyond and above that accounted for age, one burnout dimension (i.e., personal accomplishment) and one engagement dimension (i.e., dedication). Additional analysis found that personal accomplishment and dedication mediated the link between core self-evaluations and life satisfaction. Some practical implications of the current findings for educational context are discussed
Despite the limitations, these findings provide new insights into the role of CSE as a predictor of life satisfaction among teachers, which may advance a coherent and multifaceted theoretical framework on the explanatory variables through which life satisfaction among teachers may be increased
Keywords: Calidad de vida en el trabajo; Profesores - Estrés laboral; Core self-evaluations; Teacher burnout; Engagement; Life satisfaction